Capacitação de treinadores no handebol brasileiro: a complexidade como alternativa de superação do modelo técnico-linear - Calegari, Décio Roberto (2002)
This research has investigated the reasons that prevented the transformations of Brazilian handball s quantity progress, recognized internationally by International Handball Federation by conceding to Brazil Hans Bauman Trophy as the country that more developed handball in the nineties, in international victories, that is, why too many participations in World Championships did not permit Brazilian Teams to get, at least, one place on the podium (one medal), since Brazil, as Russia, was the only country to take part in all World Championships during the time mentioned above. With a 24-year experience with the modality and acting in all possible levels of sports practice (athlete, referee, coach and manager) the author could accompany Brazilian handball s evolution and verify the importance of the coach in the context of handball s development opinion shared by several authors: Greco (1995), Czewerniski (1993), Marques (2000), Bota and Evoluet (2000). He establishes, as hypothesis for the solution, the necessity of overcoming the present model of qualification for Brazilian handball coach, characterized by punctual actions, fragmentation and importation of models which are not adequate to Brazillian reality, reason for why the quantity progress was not transformed in international victories. Identified the importance of the coach s role and testified the coach-class anxiety for changes in the present reality, the author based his discussion about this reality on the theoretical reference of Complexity proposed by Edgar Morin (2002, 2001, 2000a, 2000b), using the whole property of knowledge as a central category, so that the coach to be qualified can overcome body-mind duality, understand the relations and interactions that the multiple dimensions of the sports practice can provide and develop the ability of electing the pertinent knowledge to the construction of a conscious practice able to generate conscious people. The author bases contumacious critique to the line-thecnical model of acquiring knowledge, predominant in the Brazilian handball coach s qualification, and rests on investigative/reflexive model to construct a propose that intends to estimulate curiosity and spread investigation.